Rancang Bangun Sistem Informasi Pemesanan Berbasis Web dengan Metode Pending Order Pada Wingko Babat Pratama - Elsandhy, Irwan; Sugiyamta, S (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Wingko Babat Pratama is a typical Semarang souvenir producer located at Jalan Tumpang XIV, Gajahmungkur, Semarang City. Currently, the ordering system at Wingko Babat Pratama still uses traditional methods to serve customers, including stock management, ordering, and generating sales reports. This research aims to develop a more modern ordering website by utilizing the CodeIgniter 3 Framework and applying the Pending Order method. This method gives buyers the opportunity to get a service schedule, with priority given to customers who place orders early within a certain time limit. The result of this research is a system that includes stock management, ordering, and sales report generation, which is expected to improve service quality at Wingko Babat Pratama Semarang